Parkin, an E3 ubiquitin ligase, enhances airway mitochondrial DNA release and inflammation. Issue 9 (4th June 2020) - Dimasuay, Kris Genelyn; Schaunaman, Niccolette; Martin, Richard J; Pavelka, Nicole; Kolakowski, Christena; Gottlieb, Roberta A; Holguin, Fernando; Chu, Hong Wei
Abstract : Introduction: Parkin (Park2), an E3 ubiquitin ligase, is critical to maintain mitochondrial function by regulating mitochondrial biogenesis and degradation (mitophagy), but recent evidence suggests the involvement of Parkin in promoting inflammation. In the present study, we determined if Parkin regulates airway mitochondrial DNA (mtDNA) release and inflammatory responses to type 2 cytokine interleukin (IL)-13 and allergens. Methods: We measured Parkin mRNA expression in brushed bronchial epithelial cells and mtDNA release in the paired bronchoalveolar lavage fluid (BALF) from normal subjects and asthmatics. Parkin-deficient primary human tracheobronchial epithelial (HTBE) cells generated using the CRISPR-Cas9 system were stimulated with IL-13. To determine the in vivo function of Parkin, Parkin knockout (PKO) and wild-type (WT) mice were treated with IL-13 or allergen (house dust mite, HDM) in the presence or absence of mtDNA isolated from normal mouse lungs. Results: Parkin mRNA expression in asthmatic airway epithelium was upregulated, which positively correlated with the levels of released mtDNA in BALF. IL-13-stimulated HTBE cells increased Parkin expression. Moreover, IL-13 induced mtDNA release in Parkin-sufficient, but not in Parkin-deficient HTBE cells. PKO (vs WT) mice attenuated airway mtDNA release and inflammation following IL-13 or HDM treatments. mtDNA amplified airway inflammation in mice treated with IL-13 or HDM. Notably, Parkin also mediated mtDNA-induced exacerbation of airway inflammation. Conclusion: Our research findings suggest that Parkin promotes mtDNA release and inflammation in airways, thus improving our understanding of the complex role of Parkin and mitochondrial dysfunction in asthma pathogenesis.